Foresight of Coronavirus (COVID-19) Opportunities for a Better World - Ahmed, Dunya; Buheji, Mohamed Jasim (Journal of Economic, Administrative and Legal Sciences, 2021)
Throughout history, epidemics gave humans many challenges, but yet also brought with it many visible and hidden opportunities. The Coronavirus (COVID-19) is no except, and in this paper, we foresight the opportunities for a better world that this deadly crisis brings to us. We review different opportunities that this virus and similar recent incidents, like SARS, brought to our life. Then, we pause to visualise through rethinking, redefining and reframing the hidden opportunities inside the (COVID-19) and similar coming problems and challenges. This "think outside of the box" paper create new pathways toward more inspiring economies that would address the key elements we started to miss in our development journey. Integrating future foresight into such problem-solving attempts could create for us more future-informed generations that take participatory actions towards humans’ complex challenges with high availability and preparedness. The paper concludes with a proposed framework to exploit the opportunities of such a complex crisis while mitigating its risks. Further studies are highly recommended if we are to see solutions that could save humanity from the coming crisis.
Keywords: Corna virus (Covid 19); hidden opportunities; visible opportunities; solving complex problems; epidemic; risk mitigation; human preparedness; resilient societies; deadly diseases; crisis management